ANALISIS KONTRIBUSI, EFEKTIVITAS, EFISIENSI DAN POTENSI RETRIBUSI PARIWISATA TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN SRAGEN - Devi Lolita, Suharno & Bambang Widarno (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
This study aims to analyze the contribution, effectiveness, efficiency and potential of tourism retribution to local revenue in Sragen regency. This research uses quantitative data type. Source of data in this research is secondary data, that is data in the form of local revenue, which is arranged in the form of annual report published by related party that is Central Bureau of Statistic and Disparpora (Department of Youth, Sport and Tourism of Sragen Regency) Year 2013 – 2017. Using analytical tools: growth analysis, potential analysis, effectiveness analysis with methods of analysis of tourism retribution effectiveness, analysis of tourism retribution efficiency, analysis of rill potential of tourism retribution and contribution analysis of tourism retribution. analysis of effectiveness of levy amount of realization into category very effective and reach 1,10%. The ratio of Efesien levy tourism in Sragen Regency 2013 - 2017 is classified as inefficient and less efficient. It happens because there is realization of retribution of tourism in Sragen Regency 2013 – 2017 is greater than the cost of collection. This is due to a considerable difference between revenues and collection fees. the real potential of tourism revenue retribution from 2013 - 2017 is unstable in 2013 amounting to Rp 102.340.218.000,00, in 2014 amounting to Rp 59.175.222.000,00, in 2015 amounting to Rp 65.908.374.000,00, in 2016 Rp 56.036.382.000,00, in 2017 amounting to Rp 59.379.204.000,00. the average contribution of tourism retribution to the Sragen District Original Income in 2013 – 2017 amounted to 4,8% category well above 40%. Keywords: local revenue, contribution, effectiveness, efficiency, potential of tourism retribution.